Blockchain in Life Sciences - Charles, Wendy (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book highlights the latest advances on the implementation and adaptation of blockchain technologies in real-world scientific, biomedical, and data applications. It presents rapid advancements in life sciences research and development by applying the unique capabilities inherent in distributed ledger technologies. The book unveils the current uses of blockchain in drug discovery, drug and device tracking, real-world data collection, and increased patient engagement used to unlock opportunities to advance life sciences research. This paradigm shift is explored from the perspectives of pharmaceutical professionals, biotechnology start-ups, regulatory agencies, ethical review boards, and blockchain developers. This book enlightens readers about the opportunities to empower and enable data in life sciences.
1. Introduction to Blockchain Technology -- 2. Blockchain in Academic Research -- 3. Blockchain in Pharmaceutical Research -- 4. Blockchain in Device Research -- 5. Blockchain in Genomics Research -- 6. IoT Integration in Life Sciences -- 7. Blockchain in Government Research -- 8. Using AI with Blockchain.
Keywords: Blockchains (Databases).; Security systems; Internet of things; Quantitative research; Medical care; Artificial intelligence; Blockchain; Security Science and Technology; Internet of Things; Data Analysis and Big Data; Health Care; Artificial Intelligence